Characterisation of high-frequency noise in graphene FETs at different ambient temperatures - Li, Junjie (My University, 2019)
Graphene is a promising channel material for high-frequency field-effect transistors, owing to its intrinsically high carrier velocity and purely two-dimensional structure. At high frequencies, the noise originated in device itself, especially the thermal noise, becomes very crucial for the performance of transistors. The thermal noise can be influenced by ambient temperature or self-heating due to high drain bias. This motivates the study of the effect of temperature on the noise performance of graphene field-effect transistors (GFETs). In this thesis, the results on high-frequency noise characterisation and modelling of the GFETs at different temperature and bias conditions are presented. The basic idea and main procedures of high-frequency noise modelling are based on Pospieszalski’s noise model. Two different high-frequency noise characterisation techniques, i.e., the Y-factor and cold-source methods, and two calculation methods of highfrequency noise parameters, i.e., the source-pull and 50 ohm impedance termination (F50) methods, have been analysed and discussed. The high-frequency noise of the GFETs at an ambient temperature range from -60 C to 25 C is presented. The minimum noise figure (Fmin) of the GFETs decreases with the drain bias and saturates above approximately -1 V due to the carrier mobility saturation in the channel. The noise performance shows a rather strong dependence on both temperature and gate bias mainly due to the change of carrier density and the contact resistance. The minimum noise figure (Fmin) is 1.2 dB at 6.5 GHz at room temperature, which is comparable with that of the best metal-semiconductor field effect transistors. And it decreases down to 0.3 dB at 8 GHz for an ambient temperature of -60 C. An empirical noise model for the GFETs considering both temperature and gate voltage has been proposed and verified by the experimental results. In conclusion, a way to characterise the temperature dependence of noise performance of the GFETs is discussed, which allows for further development of low-noise GFETs for high-frequency applications.
Keywords: graphene, GFET, noise characterisation, thermal experiments, minimum noise figure, F50 method, field effect transistors, microwave electronics